Towards the traffic hole problem in VANETs - Song, Chao (2013)
The data delivery in Vehicular Ad-hoc Networks which is based on the infrastructure-less vehicle-to-vehicle (V2V) communications, is sensitive to the traffic flows along the roads. However, the traffic flow may be interrupted by the traffic control system, and a gap appears to block the data delivery along the traffic flow. We term it as a traffic hole problem, which will drastically affect the data delivery along each road. For mitigating the problem, we investigate the signal operations at the intersections to adjust the traffic flows moving into the roads.